Analisis Kualitas Pelayanan Publik Pada Layanan Penyelesaian Perselisihan Hubungan Industrial di Dinas Tenaga Kerja Kota Bengkulu - Melly Dwi Karisma; Rosidin Rosidin; Titi Darmi (JOPPAS: Journal of Public Policy and Administration Silampari, 2023)
ABSTRACT:This study aims to determine the quality of public services in the Industrial Relations Dispute Settlement service at the Bengkulu City Manpower Office. This research is a descriptive study using a qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation techniques. The research informants in this study were 4 employees of the Industrial Relations Dispute Settlement Section, 2 people from the community who provided services at the Bengkulu City Manpower Office. The data analysis technique used is an interactive model. Checking the validity of the data is done by triangulation of sources and methods.The results of the study show that the implementation of public service quality in Industrial Relations Dispute Settlement services at the Bengkulu City Manpower Office is seen from the aspects of Reliability, Responsiveness, Assurance, Empathy, Tangibles. (1) The community is satisfied with the services provided at the Industrial Relations Dispute Settlement Service Section at the Bengkulu City Manpower Office in terms of reliability, reliability in the accuracy of the service process (2) employees who are ready to help people who need special services, people who minimal information, with officers who convey information by communicating well with the community. (3) Security at the Bengkulu City Manpower Service Office has provided good service quality, by providing a sense of security to people who perform public services, and ensuring secure data storage. (4) The Bengkulu City Manpower Office provides an aspect of empathy with a pleasant impression, this can be seen from the attitude of explaining as clearly as possible regarding service procedures and applicable SOPs. (5) The tangibles aspect of the service room and waiting room is sufficient, with waiting chairs and tables, but the mediation room which is not spacious plus there is a table inside sometimes makes the room cramped when there are many people in it. Keywords: Quality, Public Service, Department of Manpower